2023
DOI: 10.14336/ad.2023.0823-1
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-Derived Extracellular Vesicles for Ischemic Stroke: Therapeutic Potential and Prospective

Abstract: Stroke is a leading cause of death and disability in the world. Astrocytes are special glial cells within the central nervous system and play important roles in mediating neuroprotection and repair processes during stroke. Extracellular vesicles (EVs) are lipid bilayer particles released from cells that facilitate intercellular communication in stroke by delivering proteins, lipids, and RNA to target cells. Recently, accumulating evidence suggested that astrocyte-derived EVs (ADEVs) are actively involved in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 247 publications
(275 reference statements)
0
3
0
Order By: Relevance
“…Glial activation is a double-edged sword, whereby its acute expression may be beneficial [47], but when it occurs chronically, then such gliosis may exacerbate stroke outcomes [48]. Moreover, extracellular vesicles have been implicated in the neuroprotective function of glial cells [49]. In a similar fashion, both neurogenesis and angiogenesis are established neuroprotective and regenerative mechanisms for stroke, especially in the repair of the NVU [50][51][52], with extracellular vesicles becoming widely recognized as contributing to these therapeutic responses [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Glial activation is a double-edged sword, whereby its acute expression may be beneficial [47], but when it occurs chronically, then such gliosis may exacerbate stroke outcomes [48]. Moreover, extracellular vesicles have been implicated in the neuroprotective function of glial cells [49]. In a similar fashion, both neurogenesis and angiogenesis are established neuroprotective and regenerative mechanisms for stroke, especially in the repair of the NVU [50][51][52], with extracellular vesicles becoming widely recognized as contributing to these therapeutic responses [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…(33)(34)(35). Exosome cytoplasm involves microRNA (miRNA), long noncoding RNA (lncRNA), messenger RNA (mRNA), proteins, lipids, and lots of other active ingredients (36)(37)(38). Exosomes may deliver the active ingredients, which they convey to the target cells through mutual fusion with the cell membranes of the recipient cells, cytosis, and other modes of action to impact the function of recipient cells (39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, literature on post-stroke EV cargo is predominantly focused on microRNAs, and investigations of the protein content are relatively rare [ 41 ]. Recent evidence suggested that astrocyte-derived EVs (ADEVs) mediate numerous biological processes in stroke, including neuroprotection and neurorepair [ 44 ]. In this pilot study, we aimed to release an ADEV profile of IS patients, focusing on the GFAP as the cargo protein of these EVs in dynamics: 24 h (D1), 7 days (D7), and one month (M1) following the onset of IS.…”
Section: Introductionmentioning
confidence: 99%